1999
DOI: 10.1074/jbc.274.29.20657
|View full text |Cite
|
Sign up to set email alerts
|

Src-family Tyrosine Kinases in Activation of ERK-1 and p85/p110-phosphatidylinositol 3-Kinase by G/CCKBReceptors

Abstract: We have analyzed in Chinese hamster ovary cells the upstream mediators by which the G protein-coupled receptor, gastrin/CCK B , activates the extracellular-regulated kinases (ERKs) and p85/p110-phosphatidylinositol 3-kinase (PI 3-kinase) pathways. Overexpression of an inhibitory mutant of Shc completely blocked gastrinstimulated Shc⅐Grb2 complex formation but partially inhibited ERK-1 activation by this peptide. Expression of Csk, which inactivates Src-family kinases, totally inhibited gastrin-induced Src-like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
81
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(88 citation statements)
references
References 46 publications
5
81
2
Order By: Relevance
“…The mitogen-activated protein kinases, ERK1/2, Jun kinase, and p38 MAPK, as well as phosphatidylinositol 3-kinase, are known targets of gastrin. Several groups, including ours, have documented the contribution of upstream Src and Fak family tyrosine kinases in the activation of these pathways (3)(4)(5)(6).…”
mentioning
confidence: 99%
“…The mitogen-activated protein kinases, ERK1/2, Jun kinase, and p38 MAPK, as well as phosphatidylinositol 3-kinase, are known targets of gastrin. Several groups, including ours, have documented the contribution of upstream Src and Fak family tyrosine kinases in the activation of these pathways (3)(4)(5)(6).…”
mentioning
confidence: 99%
“…3 Mitogen-activated protein kinases, ERK1/2, Jun kinase and p38MAPK, as well as the phosphatidylinositol 3-kinase (PI3K) and early responsive genes (c-fos, c-myc and c-jun), are known targets of gastrin. [4][5][6][7] Several groups including ours, have documented the contribution of Src and focal adhesion kinase (Fak) families' tyrosine kinases upstream the activation of these pathways. 4,8 The role of gastrin and CCK2 receptors as positive regulators of proliferation of normal gastrointestinal tissues is now well recognized.…”
mentioning
confidence: 99%
“…[4][5][6][7] Several groups including ours, have documented the contribution of Src and focal adhesion kinase (Fak) families' tyrosine kinases upstream the activation of these pathways. 4,8 The role of gastrin and CCK2 receptors as positive regulators of proliferation of normal gastrointestinal tissues is now well recognized. A number of reports have also suggested that amidated gastrin may be a growth factor for gastrointestinal cancers.…”
mentioning
confidence: 99%
“…Notably, volumesensitive tyrosine kinases have been shown to modulate the trafficking of epidermal growth factor receptors in liver cells (12); both insulin receptor and p60 c-src activities are closely associated with PI 3-kinase, which is known to regulate exoand endocytosis (11,33). To assess the possibility that membrane trafficking events may contribute to the NSC response, two complementary approaches were utilized.…”
Section: P60 C-src Represents a Candidate Volume-sensitive Tyrosine Kmentioning
confidence: 99%